Influência do material e técnica de obturação endodôntica na resistência à fratura de raízes dentais humanas - Nina Neto, Felix (2009)
Gutta-percha, in combination with a variety of sealers, is the most commonly used material for root canal filling. This association presents no adhesiveness to the root structure. Resilon cones and resinous cement (Epiphany) were introduced on the market that, in association with a self-conditioning primer, would alow a solid monoblock to be obtained. The Resilon/Epiphany system forms a monoblock within the canals that bonds to the dentin walls. It has potential to strengthen the walls against fracture. The material was proposed as an alternative to gutta-percha. The purpose of this in vitro study was to evaluate the fracture resistance of root canals filled with gutta-percha/ AH Plus and root canals filled with Resilon/Epipanhy system. Sixty extracted single rooted teeth were selected. The teeth were randomly categorized into 6 groups of 10 teeth each as follows: Group I: teeth without endodontic treatment; Group II: teeth were instrumented but without endodontic obturation; Group III: teeth were instrumented and obturated with gutta-percha in conjunction with AH Plus sealer and obturated with lateral condensation technique; Group IV: teeth were instrumented and obturated with gutta-percha in conjunction with AH Plus sealer and obturated with hybrid Tagger`s techinique; Group V: teeth were instrumented and obturated with Resilon/Epiphany system and obturated with lateral condensation technique; Group VI: teeth were instrumented and obturated with Resilon/Epiphany system and obturated with hybrid Tagger`s technique. The roots were submited to the compressive test. A Kratos Universal Testing Machine was used to apply a load to each specimen at a crosshead speed of 0,5mm per minute until the root fracture. The results were submited to ANOVA test ( 5%) and Tukey test. With respect to the fracture resistance there was no statiscally significant difference between the group filled with gutta-percha and the Resilon/Epiphany system. However, the group VI showed statistically significant difference when compared with group I and group II. The presence of the endodontic material is very important to maintenance the good fracture resistance, because the group II showed the worst results. The thermoplastic technique presented better results, but within statistically significant differences.